FECAL SLUDGE MANAGEMENT OF DUHOK CITY AND 4 IDPS AND REFUGEES CAMPS - KOCHARY, SHAWKAT AHMED (Journal of Duhok University, 2021)
This study aims to assess the condition of fecal sludge management (FSM) services of non-sewered (on-site) sanitation systems in Duhok city and Chamishko, Kaparto2, Sharia IDPs and Domiz1 refugees camps. Duhok city was selected as a case study while other locations were selected for their formally temporal status besides their difference in location, size, and level of existing proper service delivery. Shit flow diagrams (SFD) for on‐site sanitation systems of interested areas were produced to identify the service outcomes and where improvements are needed to eliminate the negative impacts of FS on both public health and the environment. The study revealed that sanitation delivery services were at very good level in Kabartu2 camp as it has a wastewater treatment plant WWTP of 900 m3 /day capacity and in Sharia camp as it has a (Package Sewage) treatment plant of 1760 m3 /day capacity. In Domiz1 camp, the sanitation services were at poor level even though 25% of its generated wastewater transports to Kabartu2 WWTP for treatment. Similarly, the sanitation service level in both Duhok city and Chamishko camp were poor and very poor respectively where urgent improvements are needed. Recommendations were proposed to the decision makers of local authority to take proper actions.